TiS3 Transistors with Tailored Morphology and Electrical Properties. (13th March 2015) - Island, Joshua O.; Barawi, Mariam; Biele, Robert; Almazán, Adrián; Clamagirand, José M.; Ares, José R.; Sánchez, Carlos; van der Zant, Herre S. J.; Álvarez, José V.; D'Agosta, Roberto; Ferrer, Isabel J.; Castellanos‐Gomez, Andres
<x xml:space="preserve">Abstract</x> Control over the morphology of TiS 3 is demonstrated by synthesizing 1D nanoribbons and 2D nanosheets. The nanosheets can be exfoliated down to a single layer. Through extensive characterization of the two morphologies, differences in the electronic properties are found and attributed to a higher density of sulphur vacancies in nanosheets, which, according to density functional theory calculations, leads to an n‐type doping. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>